Utilisation of Concept Maps in Geography Education Research: A Systematic Review - Vanda Pivarníková (European Journal of Geography)
Concept maps are graphical representations of students’ knowledge and understanding, used for the development of meaningful learning. In geographical education, they can support the visualisation of processes among Earth systems and the development of systems thinking. This systematic review examines 40 empirical studies (2003–2023), written in English and found in the Scopus and Web of Science databases. The aim of the literature review was to analyse and categorise the most common uses of concept maps in geography education research, focusing on the research, interaction and application issues of concept maps in relation to geography and the students creating them. The results show that concept maps were predominantly used as an assessment tool to reveal conceptual changes post-intervention. The most frequently mapped topic was climate change and other human–environment interactions. Concept maps were primarily used to study general pedagogical problems, less to explicitly research geographical education. This review highlights the role of concept maps in geography education, and their potential and limitations in efficient implementation.